Novel banana lectin CAR-T cells to target pancreatic tumors and tumor-associated stroma. Issue 1 (18th January 2023) - McKenna, Mary K; Ozcan, Ada; Brenner, Daniel; Watanabe, Norihiro; Legendre, Maureen; Thomas, Dafydd G; Ashwood, Christopher; Cummings, Richard D; Bonifant, Challice; Markovitz, David M; Brenner, Malcolm K
Abstract : Background: Cell therapies for solid tumors are thwarted by the hostile tumor microenvironment (TME) and by heterogeneous expression of tumor target antigens. We address both limitations with a novel class of chimeric antigen receptors based on plant lectins, which recognize the aberrant sugar residues that are a 'hallmark' of both malignant and associated stromal cells. We have expressed in T cells a modified lectin from banana, H84T BanLec, attached to a chimeric antigen receptor (H84T-CAR) that recognizes high-mannose (asparagine residue with five to nine mannoses). Here, we tested the efficacy of our novel H84T CAR in models of pancreatic ductal adenocarcinoma (PDAC), intractable tumors with aberrant glycosylation and characterized by desmoplastic stroma largely contributed by pancreatic stellate cells (PSCs). Methods: We transduced human T cells with a second-generation retroviral construct expressing the H84T BanLec chimeric receptor, measured T-cell expansion, characterized T-cell phenotype, and tested their efficacy against PDAC tumor cells lines by flow cytometry quantification. In three-dimensional (3D) spheroid models, we measured H84T CAR T-cell disruption of PSC architecture, and T-cell infiltration by live imaging. We tested the activity of H84T CAR T cells against tumor xenografts derived from three PDAC cell lines. Antitumor activity was quantified by caliper measurement and bioluminescence signal and used anti-human vimentin to measure residual PSCs. Results: H84T BanLec CAR was successfully transduced and expressed by T cells which had robust expansion and retained central memory phenotype in both CD4 and CD8 compartments. H84T CAR T cells targeted and eliminated PDAC tumor cell lines. They also disrupted PSC architecture in 3D models in vitro and reduced total tumor and stroma cells in mixed co-cultures. H84T CAR T cells exhibited improved T-cell infiltration in multicellular spheroids and had potent antitumor effects in the xenograft models. We observed no adverse effects against normal tissues. Conclusions: T cells expressing H84T CAR target malignant cells and their stroma in PDAC tumor models. The incorporation of glycan-targeting lectins within CARs thus extends their activity to include both malignant cells and their supporting stromal cells, disrupting the TME that otherwise diminishes the activity of cellular therapies against solid tumors.